Tingkatkan Aktivitas Belajar Geografi: Implementasi Model Project- Based Learning dengan Media Aplikasi Canva di Kelas X SMA N 1 Seririt - Kadek Diah Arita Dewi; I Putu Ananda Citra; I Gede Astra Wesnawa (Journal on Education, 2024)
Student activities in the learning process are not only limited to listening and taking notes. The more activities students do during learning, the quality of the learning process will increase. This research aims to examine the impact of the Project-Based Learning model with the support of the Canva application on student learning activities in geography subjects. The research subjects consisted of five classes The research design used was One Group Pretest-Posttest Design. Data collection was carried out through observation and documentation techniques. Data analysis was carried out descriptively and quantitatively, with hypothesis testing using the T-test and simple linear regression test. The research results show that there is a positive and significant influence from implementing the Project-Based Learning model with the support of the Canva application on student learning activities in geography subjects.